2020
DOI: 10.1124/jpet.120.000321
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod Phosphate (FTY720-P) Activates Protein Phosphatase 2A in Human Monocytes and Inhibits Monosodium Urate Crystal–Induced Interleukin-1β Production

Abstract: Gout is a chronic inflammatory arthritis caused by monosodium urate monohydrate (MSU) crystal deposits in joints of lower limbs. Phagocytic uptake of MSU crystals by joint-resident macrophages and recruited circulating monocytes results in IL-1 expression and production. Current acute gout treatments have serious toxicities and suffer suboptimal clinical outcomes. Protein phosphatase 2A (PP2A) plays an important role in regulating signaling pathways relevant to inflammation. We hypothesized that innate immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…To date, the best known PP2A activator is the sphingosine analog FTY720, FTY720 has other roles, most notably as a functional antagonist of the S1P pathway. Previous study has shown that the active metabolites of FTY720 can activate PP2A and inhibit the production of IL-1b induced by MSU crystals (37), but the molecular mechanism of its inhibition of IL-1b production has not been thoroughly explored. Arctigenin is a natural product, so we chose to study the effect of ATG on the inflammatory response induced by MSU crystals and its molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the best known PP2A activator is the sphingosine analog FTY720, FTY720 has other roles, most notably as a functional antagonist of the S1P pathway. Previous study has shown that the active metabolites of FTY720 can activate PP2A and inhibit the production of IL-1b induced by MSU crystals (37), but the molecular mechanism of its inhibition of IL-1b production has not been thoroughly explored. Arctigenin is a natural product, so we chose to study the effect of ATG on the inflammatory response induced by MSU crystals and its molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…To further characterize the contribution of PP2A to rhPRG4’s mechanism of action, we evaluated the effect of co-incubating rhPRG4 with okadaic acid, a potent PP2A inhibitor ( 30 ). Normal and gout PBMCs and THP-1 monocytes were primed with a TLR2 ligand, Pam3CSK4, for 24h prior to adding urate crystals, as PBMCs and monocytes fail to secrete significant IL-1β in response to crystals alone ( 22 , 26 ). Across all experiments, assays were performed with two technical replicates per experimental group, with 3-4 independent experiments for THP-1 monocytes.…”
Section: Methodsmentioning
confidence: 99%
“…THP-1 monocytes were treated with Pam3CSK4 (1μg/mL) for 24h followed by MSU crystals (200μg/mL) ± IL-1RA (250ng/mL) or rhPRG4 (200μg/mL) for 6h. IL-1β gene expression was performed as previously described ( 26 ), using commercially available primers and probes for IL-1β (Hs01555410_m1) and β-actin (Hs00194899_m1) (ThermoFisher Scientific, USA), and the cycle threshold (Ct) value of IL-1β was normalized to the Ct value of β-actin in the same sample, and the relative expression in the different experimental groups compared to untreated controls was computed using the 2 -ΔΔCt method ( 26 ). In another set of experiments, cells were treated and subsequently collected and lysed using RIPA buffer + 1% protease inhibitor (ThermoFisher Scientific), and cell lysate total protein was determined using the micro-BCA assay kit (Sigma Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations